Treatability studies on wastewater from textile dyeing factories in Bursa, Turkey - Çiner, Fehiman (International Journal of Environment and Pollution, 2003)
The textile industry is one of the most rapidly developing industries in Turkey. It generates a large amount of wastewater, with corresponding concerns about pollution. The main sources of pollution in wastewater are the dyeing and finishing processes. The dyestuffs and polyvinyl alcohol (PVA) are the main refractory organics of concern in terms of meeting more stringent effluent standards of chemical oxygen demand (COD) and colour. In this study, wastewaters from textile dyeing factories in Bursa were characterized, and physical, chemical and biological treatability studies were carried out. In the physical and chemical studies, 60-80% COD, 80% suspended solids (SS) and 10-92% turbidity removal efficiencies were obtained. In the biological studies, 90% COD and 40% SS removal were obtained. The initial soluble inert COD of wastewater was determined by using comparison methods. The initial inert COD of wastewater and the microbial product concentration were determined as 37 mg/I and 13 mg/l, respectively.